Non-linear analysis of seismic performance of low-rise concrete buildings in Indonesia. Issue 1 (July 2021) - Suwondo, Riza; Mangindaan, Dave; Cunningham, Lee; Alama, Sohaib
Abstract: It is well known that the parts of Indonesia are considered as moderate to high seismicity zones. The Indonesian Standard for seismic design has been developed based on linear analysis which is the most common approach in seismic analysis. This study presents an evaluation of a low-rise reinforced concrete building using non-linear analysis. The main purpose of this study is to investigate the actual safety level of a concrete building seismically designed according to the Indonesian Standard. The results showed that the building satisfies the intended objectives of the seismic design both in terms of global and local response.